استخدام اسلوب تحليل التعادل في تحليل حساسية ربحبة المشاريع الاستثمارية: دراسة حالة مشروع " انتاج زيت الزيتون" - (:unkn) unknown (University of Eloued جامعة الوادي, 2018)
ملخص: تهدف هذه الدراسة إلى تسليط الضوء على أسلوب تحليل التعادل باعتباره أداة مهمة في مجال تخطيط الأرباح وشكل من أشكال تحليل الحساسية حيث يمكن من فحص تأثير تغيرات عوامل التكلفة، الحجم والسعر على الربحية، ولهذا الغرض تم اختيار مشروع إنتاج زيت الزيتون بولاية سوق أهراس والممول من الوكالة الوطنية لدعم وتشغيل الشباب كنموذج. أظهرت نتائج الدراسة أن المشروع يتمتع بمخاطرة منخفضة إذ تبين أن نقطة التعادل للمشروع بحدود 24 % من مبيعاته وهي نسبة منخفضة توضح بأن المشروع أمامه فرصة كبيرة لتعظيم الأرباح وأن هامش الأمان هو بحدود 76 %. كما أظهر تحليل حساسية الربحية للعوامل المؤثرة بأن المشروع حساس نوعا ما لعامل السعر في حين أنه قليل الحساسية لعاملي الكمية المباعة والتكلفة المتغيرة وهذا ما أكدته نتيجة التحليل باستخدام نقطتي التعادل المحاسبية والمالية. Abstract: : This study aims to highlight the method of break-even analysis as an important tool in the field of profit planning and a form of sensitivity analysis, by which, it is possible to examine the impact of changes in cost factors, size and price, on profitability . For this purpose, the olive oil production project, located in Souk Ahras and funded by the National Agency for Youth Support and Employment, was selected as a model. The results of the study showed that the project has a low risk, and its break-even point is around 24% of sales which is a low percentage offers to project a great opportunity to maximize profits, and the safety margin is up to 76%. The profitability sensitivity analysis also showed that the project is a bit sensitive to the price factor more than the factors of sold quantity and variable cost. This result is confirmed by the the accounting and financial Break-even points analysis.
Using the break-even analysis method to analyze the profitability sensitivity of investment projects: case study -The Project of Olive Oil Production -
مجلة رؤى المجلد الثامن العدد الثاني
Keywords: تحليل التعادل، تحليل الحساسية، مشروع إنتاج زيت الزيتون، مخاطرة.; Break-even analysis, sensitivity analysis, Olive Oil Production Project, Risk. Jel Classification Codes : D81, G21.